The complete National Geographic 110 years of National Geographic magazine on CD-ROM (National Geographic Society, 1999)
Contains all the complete issues of the National Geographic magazine from 1888 to 1998, with more than 182,000 images, 9,400 articles, 192,000 pages and 100+ years of classic advertisements.